Modulation of immune response by the acute and chronic exposure to high altitude - Facco, M.; Zilli, C.; Siviero, M.; Ermolao, A.; Travain, G.; Baesso, I.; Bonamico, S.; Cabrelle, A.; Zaccaria, M.; Agostini, C. (Medicine & Science in Sports & Exercise, 2005)
Purpose: The chronic exposure at high altitude (HA) represents an ideal model for evaluating the in vivo effects of hypobaric hypoxia. Taking advantage of the EV-K2-CNR Pyramid, this study was designed to evaluate whether acute and chronic hypoxia differently modulates the in vivo immune responses.